Numerical simulation of the effect of Ch4, H2 and diesel fuel mixture on four stroke engine - Luaibi Alrazen, Hayder Abdullah (2015)
Gaseous fuels have been investigated to be a helpful substitute in compression-ignition engine by researchers. There was extension in the ignition delay of diesel-CH4 dual-fuel mode as compared with usual diesel fuel mode. Methane has a low flame propagation speed as well as slight flammability whereas hydrogen has the extreme opposite characteristics. As such adding hydrogen can enhance methane’s combustion process making it extra convenient in diesel engine application. H2-Diesel produced many of the unwanted effects such as rapid burning rate and increased diffusivity and reduced ignition energy of hydrogen that may lead to knocking, an impact that is harmful to engine’s mechanical durability as well as safety. Methane addition has the ability to make hydrogen combustion stable and smoother which can prevent imperfect combustion. Methane can also lower the combustion temperature of hydrogen so as to repress NOx emission. In the present study, the author proposes that by adding hydrogen into methane and diesel, it can improve the combustion process. The usage of GAMBIT software was chosen to create the entire computational domain of the engine and for Computational Fluid Dynamics (CFD) the FLUENT code was used. The engine was operated under dual-fuel and tri-fuel modes with different values of excess air (λ) including 1.2, 1.4, 1.6, 1.8, 2, 2.2 and 2.4. Moreover, torque (20.18 N.M),intake temperature (330 K), and engine speed (2000 rpm) were taken constantly at an atmospheric pressure. Diesel-CH4, diesel-H2 dual-fuel operation, and diesel-CH4-H2 tri-fuel operation were employed in this work. H30-M70, H50-M50 and H70-M30 were designed for the mixtures percent of hydrogen to methane which are 30:70, 50:50 and 70:30 %, respectively, and then used them in the simulations. Due to knocking, the maximum quantity of substitution by hydrogen was limited to 50%. Therefore, the quantity of diesel was employed 50 percent by mass from the total fuel at diesel mode and the other 50 percent was substituted by the methane and hydrogen as mentioned above. The addition of gaseous fuels increases the peak in-cylinder pressure and peak temperature at both the low and medium values of the exceed air. Meanwhile, at high value of exceeds air, no effects on the peak temperature were noted between Diesel-H70-M30 for tri mode and Diesel-H2 for dual mode. Compared with CH4-Diesel at 2.4 exceed air, the peak pressure increases by 28.57% and 33.414% by way of adding the limit value of hydrogen to methane,such as H30-M70 and H50-M50, respectively. Compared with H50-M50, it begins to decrease by 0.726% and 3.81% with H70-M30 and H2-Diesel operations, respectively, that may be because of the low value of fuels in air compared with other cases. The addition of methane in hydrogen produces a smoother combustion of hydrogen and ascertains that the engine is safe and it has mechanical durability. Tri-fuel and dual-fuel modes have a similar suppression effect on CO2 emission but with hydrogen there is more reduction in CO2 emission compared with methane. However, Diesel-H2-CH4 operations decrease the CO emission compared with the Diesel-CH4 operation and decrease the NO emission compared with the Diesel-H2 operation at every exceed air. High hydrogen fraction in methane (H70-M30) is suggested at all exceeds air in order to reduce CO/CO2 emissions, whereas low hydrogen fraction in methane (H30-M70) can suppress the uncontrolled hydrogen combustion and limit the increment of the NO emission.